Pub Psychic Nights: Spiritual and Social Transformation Beyond Institutional Boundaries - Starkey, Caroline (Implicit religion, 2023)
This article explores pub psychic nights in Britain. The audience of these events are predominantly working- class women who gather in local pubs and social clubs to participate in spirit communication led by a medium and/or psychic. Drawing on qualitative data from 16 interviews and four participant observations we examine the social and spiritual significance of these events for the audience, arguing that they have a profound impact in helping people deal with grief and loss, extending far beyond mere entertainment. We further argue that pub psychic nights create an opportunity to address existential questions and seek comfort outside of traditional religious institutions. We demonstrate how these nights blur the boundaries between the ordinary and the extraordinary and transform historically male-dominated pub spaces into local hubs of female- led spirituality. This research contributes to a deeper understanding of contemporary spiritual practices and their significance for marginalized communities.